(untitled) (Tanzania Journal for Population studies and Development, 2023)
It is commonly accepted that teen pregnancies raise the risk of both mental and physical health problems, although, worldwide, research amply supports the impact of adolescent pregnancies on the expansion of human capital. The association implies that, in the long-run, a teenage mother’s prospects will be harmed, expanding the gender gap. The purpose of this study was to identify the risk factors of adolescent pregnancy, the health issues that they and their unborn babies must deal with, and to ascertain – through a systematic review – what additional developmental needs are brought on by early pregnancy. Nine studies were chosen to research the primary risk factors of teen pregnancy, while ten articles evaluated the negative effects of early pregnancy. A total of 19 articles, published in reliable journals between 2009 and 2021, were chosen for the study. Reviews, meta-analyses, and case studies were not chosen: only original work from reputable journals was considered. The most common causes of teenage pregnancy were found to be the lack of formal education, ignorance of how contraception should be handled, ignorance of sex and pregnancy risks, and early marriage. The analysis revealed that neonatal disorders such as eclampsia, severe anaemia, haemorrhage, and premature birth are more common among adolescent mothers. The results show that neonates and adolescent mothers both have negative impacts from early pregnancies. The study emphasizes the importance of sex education and campaigns to promote the use of contraception. Also, proper physical care and psychosocial support through health care agencies should be promoted. Keywords:, , , and